2018
DOI: 10.1016/j.lpm.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Production scientifique des CHU-CHR en 2006–2015 : évolutions et positionnement national

Abstract: Remerciements : les auteurs remercient tous les relecteurs de ce manuscrit qui ont contribué à son amélioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…With the help of various programs implemented by the Ministry of Higher Education and Research to restructure research activities in France, successive strategic plans have led to the emergence of centers of excellence, in which research and public health issues are the foundation for their work in advancing the state of knowledge. Previous studies have also reported a strong increase in the number of scientific articles published in recent years in large institutions (4,5).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…With the help of various programs implemented by the Ministry of Higher Education and Research to restructure research activities in France, successive strategic plans have led to the emergence of centers of excellence, in which research and public health issues are the foundation for their work in advancing the state of knowledge. Previous studies have also reported a strong increase in the number of scientific articles published in recent years in large institutions (4,5).…”
Section: Discussionmentioning
confidence: 85%
“…Several recent bibliometric studies have evaluated scientific repercussions or temporal trends in different areas of scientific and medical research (3). Other studies have focused on the impact of publication output of one or several institutions (4,5) or at a national level (6). To the best of our knowledge, only a few bibliometric studies have been performed in the Caribbean or the French West Indies (7,8).…”
mentioning
confidence: 99%
“…The organisation enhanced feature has been selectively used in bibliometric studies to improve accuracy (Baudoin, Akiki, Magnan, & Devos, 2018). A recent study (Donner, Purnell, P. (2022) The prevalence and impact of university affiliation discrepancies between four bibliographic databases -Scopus, Web of Science, Dimensions, and Microsoft Academic.…”
Section: Literature Reviewmentioning
confidence: 99%